Pendampingan Pencatatan Transaksi Keuangan Pada Koperasi Bunga Harapan Desa Ceweng - Rita Mutiarni; Langgeng Prayitno Utomo; Siti Zuhroh (COMVICE: Journal Of Community Service, 2017)
The 1945 Constitution mandates that the prosperous prosperity be the prosperity of the people and not the prosperity of individuals or the prosperity of the enterprise; therefore, the form of business entity in question is a cooperative. Women's Cooperative (Kopwan) Bunga Harapan in Ceweng village is not only engaged in savings and loans, but starting in 2016 has started to expand its business in the provision of household goods through the unit of shops / war stalls (waserda). The activity has been running for more than 1 (one) year, however, the management of the cooperative has not been able to present the transaction record in the shop unit according to the accounting standard, so the board has difficulties in knowing the business development of the shop. To that end, the counterpart team conducts training and mentoring of financial reporting and record keeping for store / waserda units, which start in March and end in May 2017. From the training and mentoring results, shop staff / shopkeepers are familiar with the recording of daily transactions as per accounting standards for a trading company.Keywords: Cooperatives, shops, waserda, recording transactions.